The Successful Administration of Steroid in Extrahepatic Cholestasis - Winahyu, Anindya Kusuma; Prihaningtyas, Rendi Aji; Setyoboedi, Bagus; Arief, Sjamsul (Journal of Community Medicine and Public Health Research, 2023)
Biliary atresia is the most common cause of liver transplantation in children. Kasai surgery is still a bridging therapy for biliary atresia, but patients are often late for treatment. Based on the currently proposed theory, biliary atresia results from a progressive inflammatory process and progresses to fibrosis of the bile ducts. A case of a 1.5-month-old boy with prolonged jaundice followed by acholic stools and dark urine was presented. He had cholestasis, elevated GGT levels, and a liver biopsy suggesting extrahepatic cholestasis. He was treated with methylprednisolone, ursodeoxycholic acid, and vitamin supplementation was started orally. After steroid therapy, direct bilirubin levels decreased rapidly to 0.55 mg/dl on day 14. Jaundice, acholic stools, cholestasis, and liver function tests were improved. Therapeutic opportunities based on the pathogenesis of inflammation in biliary atresia using steroids may provide new opportunities for non-surgical management of biliary atresia in the early phase of the disease.